Sexual mixing patterns and anal HPV among young gay, bisexual, and other men who have sex with men and transgender women in 2 cities in the United States, 2012–2014 - Assaf, Ryan D. (Sex Transm Dis, 2020)
BACKGROUND: Human papillomavirus (HPV) is a common sexually transmitted infection. Men who have sex with men (MSM) and transgender women (TGW) are at high risk for anal HPV infection and subsequent anal cancer. This study assessed the association of partner discordances with prevalent high-risk anal HPV (HRAHPV) among MSM and TGW. METHODS: Participants were enrolled in the cross-sectional Young Men’s HPV (YMHPV) study of gay, bisexual, and other MSM, and TGW, aged 18–26 years, from two cities. Participants completed a confidential standardized computer-assisted interview and provided self-collected anal swabs for type-specific HPV DNA testing. Multivariate analyses were conducted for three discordances of interest (i.e., partner age, race/ethnicity, and concurrent partner) to calculate adjusted odds ratios (aOR) and 95% confidence intervals (CI). RESULTS: 862 participants were included for partner race/ethnicity discordance, 601 for partner age discordance, and 581 for concurrent partner analysis. Most reported being >21 years old, cisgender male, and gay. Adjusted odds of HRAHPV were not significantly increased among participants reporting partner age discrepancy >10 years (aOR:0.89; CI:0.51, 1.56), partner race/ethnicity discordance (aOR:0.88; CI:0.62, 1.24), or partner with concurrent partners (aOR:0.85; CI:0.50, 1.42), compared to those who did not. CONCLUSIONS: This analysis did not identify any partner discordances associated with HRAHPV. Since HPV infection can persist for years, sexual mixing patterns with early partners might be more relevant than the most recent sex partner. Prevalence of HRAHPV was high and could be preventable by pre-exposure vaccination, as recommended for everyone through age 26 years including MSM and TGW.